Advancing a critical social psychological perspective on women's leadership: A case illustration from the Global South. Issue 1 (28th March 2022) - Nguyen, Lan Thi; Taylor, Greig; Gibson, Paul; Gordon, Raymond
Abstract: When applied to the Global South, mainstream positivist approaches to work and organisational psychology impose alien theories of personality (the self) and leadership. In the case of women, they fail to capture the richness of their experiences of life and leadership, which are influenced by the nexus between history, power and marginalisation—for many, even oppression. The purpose of this article is to demonstrate the value of a critical social psychological approach, despite its grounding in the Global North discourse, to analyse women's leadership from a cross‐cultural context. To illustrate, we provide an empirical example of a Vietnamese woman leader's life‐story drawing on the theoretical resources from critical social psychology to interpret her experiences. When viewed from this perspective, women's leadership is understood within a dialogical space, which is prior to and more fundamental than any instrumental reason and technical rationality. It is argued that this approach resists essentialising assumptions about gender and cultural practices of leadership, providing a more liberating means to understand the life and leadership of Vietnamese women. In the final analysis, we argue that this study contributes to the nascent field of critical work and organisational psychology.